Is there None Left to Say Anything? - Moore, James F. (Zygon, 2004)
Abstract. Remarks made by Lutheran leaders in Africa indicate that the churches have not been responding to the crisis of the HIV/AIDS pandemic sufficiently. In this essay I ask how the churches would be better prepared to act and also, more broadly, how the churches act to begin with. The dialogue between religion and science can assist us with both tasks as we consider the challenge of HIV/AIDS as a focus for this dialogue. First, analysis by social scientists can uncover what problems face any effort to motivate churches to act—and, for that matter, any individual member of a church group. I argue, further, that we can discover the difficulties associated with producing action by religious communities by looking not at abstract theological ideas but by investigating the way those ideas are conveyed in worship. I explore the worship patterns of Lutherans to show what sort of view is actually produced by the week-to-week messages of liturgical texts. I contend that a different approach both to worship and to action can be produced by reconsidering our views of reality as seen through the eyes of contemporary science.